Knowledge societies --in a nutshell : information technology for sustainable development - Credé, Andreas; Mansell, Robin E.; International Development Research Centre (Canada); United Nations Commission on Science and Technology for Development (Ottawa : The Centre, 1998)
In summarizing the full-length report of the Working Group (entitled Knowledge Societies), this book focuses particularly on the dangers that will accompany a failure to develop information and communication technology (ICT) strategies tailored to the specific and changing needs of countries in the developing regions of the world. It will appeal to decision-makers and ICT producers and users, as well as to development professionals, academics, and citizens interested in development issues and the new and emerging information and communication technologies.
Cover -- CONTENTS -- FOREWORD -- INTRODUCTION -- The key opportunities -- CHAPTER 1 IDENTIFYING NEW ICT OPPORTUNITIES -- New types of learning and education -- A wired civil society -- New forms of commerce -- Opportunities for trade -- Potential uses of ICTs -- ICTs and employment -- New technical infrastructures -- CHAPTER 2 BUILDING THE CAPABILITIES -- Illiteracy44; skills44; and knowledge45;based development -- New social capabilities -- Tacit knowledge and the learning economy -- Acquiring new skills -- Lifelong learning -- Tools for building innovative knowledge societies -- CHAPTER 3 CONSTRUCTING THE INFRASTRUCTURE -- The Missing Link revisited -- Communication45;network development -- Expansion of the Internet -- Benefits of network expansion -- ICT production capacity -- Building new coalitions of resources -- CHAPTER 4 ADDRESSING KEY GOVERNANCE ISSUES -- International institutions governing ICTs -- Opening up but keeping control -- Governing trade in services and equipment -- Protecting intellectual property -- Privacy and information security -- Governance and the networld economy -- CHAPTER 5 FORMULATING ICT STRATEGIES -- Technology choices and capacity45;building -- Strategies for market liberalization -- Promoting improved access -- Harnessing ICTs for development -- Integrating ICT strategies -- Guidelines for ICT strategies -- CHAPTER 6 ICTs FOR SUSTAINABLE DEVELOPMENT -- APPENDIX I46; ACRONYMS AND ABBREVIATIONS -- ABOUT THE AUTHORS -- ABOUT THE INSTITUTIONS -- ABOUT THE PUBLISHER -- Last Page.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Information technology -- Developing countries; Technological innovations -- Developing countries; Sustainable development -- Developing countries; Technologie de l'information -- Pays en voie de développement.; Innovations -- Pays en voie de développement.; Développement durable -- Pays en voie de développement.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Information technology; Sustainable development; Technological innovations; Developing countries; Kennismaatschappij; Informatietechnologie; Duurzame ontwikkeling; Ontwikkelingslanden; Environnement -- Protection -- Pays en voie de développement.; Développement durable -- Pays en voie de développement.; Nouvelles technologies de l'information et de la communication -- Pays en voie de développement.; Innovations -- Pays en voie de développement.; information technology; telecommunications; information industry; capacity building; sustainable development; distance study; Internet; business; electronic network; employment; learning; skill; continuing education; infrastructure; international cooperation; intellectual property; data protection; access to information; statistical table; developing countries; technologie de l'information.; télécommunications.; industrie de l'information.; renforcement des capacités.; développement durable; enseignement à distance; Internet; affaires; réseau électronique.; emploi; acquisition de connaissances; qualifications; éducation permanente; infrastructure; coopération internationale; propriété intellectuelle; protection des données.; accès à l'information.; tableau statistique; pays en développement.; tecnología de la información.